Luminal Heterodimeric Amino Acid Transporter Defective in Cystinuria - Pfeiffer, Rahel (The American Society for Cell Biology, 1999)
Mutations of the glycoprotein rBAT cause cystinuria type I, an autosomal recessive failure of dibasic amino acid transport (b(0,+) type) across luminal membranes of intestine and kidney cells. Here we identify the permease-like protein b(0,+)AT as the catalytic subunit that associates by a disulfide bond with rBAT to form a hetero-oligomeric b(0,+) amino acid transporter complex. We demonstrate its b(0,+)-type amino acid transport kinetics using a heterodimeric fusion construct and show its luminal brush border localization in kidney proximal tubule. These biochemical, transport, and localization characteristics as well as the chromosomal localization on 19q support the notion that the b(0,+)AT protein is the product of the gene defective in non-type I cystinuria.